Association of body mass index with long-term outcomes after elective and semi-urgent percutaneous coronary intervention. (3rd October 2022) - Ho, J S Y; Soh, R Y H; Djohan, A H; Sim, H W; Loh, P H; Yeo, T C; Tan, H C; Chan, M Y; Sia, C H
Abstract: Background: While obesity is associated with cardiovascular mortality and morbidity, patients with higher body mass index (BMI) may have better outcomes post-percutaneous coronary intervention (PCI). This "obesity paradox" is controversial and needs clarification. Purpose: We aimed to investigate the relationship between BMI and outcomes post-PCI in an Asian cohort. Methods: A retrospective cohort study was performed on consecutive patients who underwent semi-urgent PCI for non-ST elevation myocardial infraction or unstable angina, and elective PCI for stable angina from January 2014 to December 2015 in a tertiary centre. Patients were underweight (BMI <18.5), normal weight (BMI 18.5–22.9), overweight (BMI 23–24.9), pre-obese (BMI 25–29.9) or obese (BMI ≥30), according to the WHO Asian classification. The primary endpoint was all-cause mortality. The secondary outcomes were subsequent events of stroke or transient ischemic attack, myocardial infarction (MI) and congestive cardiac failure (CCF). Results: 1, 610 patients were followed up for 3.71 (±0.97) years, 19.7% were female and mean age was 62.1 years (Table 1). BMI showed a U-shaped relationship with the incidence of death (p<0.001), MI (p=0.005), and CCF (p<0.001) (Figure 1A), which was also shown on Kaplan Meier analysis (Figures 1B-E). With reference to normal weight patients on multivariable Cox analysis, overweight (adjusted HR 0.64, 95% CI 0.42–0.97) and pre-obese (adjusted HR 0.55, 95% CI 0.38–0.80) patients had lower mortality. Underweight patients had higher risk (adjusted HR 2.12, 95% CI 1.01–4.46), while pre-obese patients had lower risk of MI (adjusted HR 0.56, 95% CI 0.34–0.92) compared to normal weight patients. Underweight and obese patients had higher risk of CCF (underweight: adjusted HR 3.05, 95% CI 1.45–6.42; obese: adjusted HR 1.86, 95% CI 1.03–3.35) compared to normal weight patients. Conclusion: Patients at the lower and upper extremes of BMI demonstrated higher risk of mortality, MI and CCF post-PCI. Funding Acknowledgement: Type of funding sources: None.